Implementing collection system recyclables in the University City of San Marcos - Vergiú Canto, Jorge Luis (2013)
This paper focuses on the need to treat urban waste inside the San Marcos university campus In the first stage, a diagnostic procedure for the collection of waste and their respective classification and quantification was performed. Of the alternatives evaluated for improving the collection system, it was determined that the installation of a waste treatment plant is the most appropriate because it will generate benefits in the field of health, academic and economic campus.